"There Isn't Really Anything around Here...": Autism, Education and the Experience of Families Living in Rural Coastal England - David Preece; Ivana Lessner Lištiaková (MDPI AG, 2021)
Autism affects over 2% of the school population in England. Education has proven to be an effective intervention strategy that improves the quality of life of children with autism and their families. However, governmental austerity policies have increased disadvantage in coastal areas of England with a detrimental impact on people with disabilities. This qualitative study explored the lives of families living with autism in rural coastal England. Mothers, fathers, grandparents and young people from 21 families living with autism in West Norfolk and Cornwall shared their experience through semi-structured interviews that were conducted in early 2019. Families identified positive and negative aspects of living in these areas, including barriers preventing access to and inclusion in education. Barriers were related to poor infrastructure, sparse specialised services (resulting in diagnostic delay and difficulties), limited autism awareness, lack of trained professionals, and the impact of austerity across health, social care and education. Families' struggles are amplified by the intersectionality of (a) autism-specific needs, (b) physical distance and small-community life related to rurality and (c) the seasonal and peripheral nature of coastal life. Access to education for children with autism in rural coastal areas of England could be improved by acknowledging and addressing the intersecting factors intensifying their marginalisation.